A Cultural Content Analysis of the EFL Textbook for Primary Education in Indonesia (NOBEL: Journal of Literature and Language Teaching, 2022)
This study attempts to investigate the cultural contents of two EFL textbooks entitled English for Elementary School Students Grade 6 and Grow with English Book 6. This research is qualitative descriptive research, particularly content analysis. This study uses the categorization of cultural aspects by Cortazzi and Jin (1999), including source culture, target culture, and International culture. Adaskou’s et al. (1990) categorization of cultural dimensions covering sociological sense, aesthetic sense, semantic sense, and pragmatic sense is also employed. The findings show that the two English textbooks present the cultural aspects and dimensions differently. English for Elementary School Students Grade 6 textbook carries out more source culture than target culture and international culture. In comparison, Grow with English Grade 6 textbook carries out more target culture than source and global cultures. The findings also reveal that the sociological sense is the most prominent sense occurring in the two textbooks compared to the aesthetic, semantic, and pragmatic senses. Therefore, from the results, it can be inferred that the proportion of the cultural content in the two textbooks is imbalanced.